TEACHERS’ BELIEFS OF USING GROUP INVESTIGATION (GI) TECHNIQUE IN TEACHING READING ANALYTICAL EXPOSITION TEXT - Mustikawati, Regita Mulia; Ahmad, Yousef Bani; Pujiawati, Nia (PROJECT (Professional Journal of English Education), 2024)
This study focuses on exploring EFL teachers' beliefs regarding the teaching of reading Analytical Exposition Text through the Group Investigation (GI) technique. Employing a qualitative approach with a case study design, the study involved two teachers from a senior high school in Karawang: one novice and one experienced. Data was gathered through semi-structured interviews featuring open-ended questions. The findings are categorized into two main areas: the origins of teachers' beliefs and their beliefs specifically about using Group Investigation for teaching reading Analytical Exposition Text. The study recommends that teachers integrate opportunities for evaluation and feedback to further enhance the efficacy of the GI technique.